Constitutional growth delay pattern of growth in velo-cardio-facial syndrome: longitudinal follow up and final height of two cases. - (:unkn) unknown (My University, 2008)
We report two patients with velo-cardio-facial syndrome (VCFS) who were admitted to our pediatric endocrinology clinic because of short stature and followed longitudinally until attainment of final height. Both patients followed a growth pattern consistent with constitutional delay of puberty with normal and near normal final height. Case 2 also had partial growth hormone (GH) deficiency and severe short stature (height SDS -3.4 SDS), but showed spontaneous catch-up and ended up with a final height of -2 SDS. These cases suggest that short stature in children with VCFS is due to a pattern of growth similar to that observed in constitutional delay of growth and puberty.